Pemanfaatan Teknologi Augmented Reality pada Sistem Pernapasan Manusia (Indo-MathEdu Intellectuals Journal, 2024)
This study explores the use of Augmented Reality (AR) technology in studying the human respiratory system using a qualitative research method of a literature approach. Augmented Reality (AR) is a technology that combines virtual objects with real environments in real-time, which can be used as a visualization tool in education. This article uses a qualitative method with a library research approach that focuses on the discussion of learning and learning. The data collection technique used in this study is reading books, recording and collecting data from various literature such as journals, documents. The stages of analysis carried out in this study include several stages, including the preparation stage, data collection stage, data reduction, data categorization, data display, and conclusion drawing. The results of the study show that the use of AR in human respiratory system education can improve students' understanding through interactive and realistic 3D visualization. In addition, AR also allows students to study the structure and function of respiratory organs in a more in-depth and engaging way. However, technical constraints, costs, and the need for training for teachers are obstacles that need to be overcome for wider implementation. This study concludes that AR has great potential as an innovative learning tool in the medical field, especially for the respiratory system, if there is adequate support in terms of technology and educational infrastructure